Base, superstructure, Underworld: Marxism and post-Marxism in Don DeLillo's Fin de Siecle fiction. Issue 8 (2nd August 2020) - Rollins, Joe
ABSTRACT: This paper argues that Don DeLillo's 1997 novel Underworld represents a concerted attempt on the author's behalf to situate himself in relation to the post-Marxist debates of the 1990s. First arguing that, contrary to popular accounts of the period, the 1990s represented a moment of intense debate regarding the future of Marxism in the twenty-first century, I read DeLillo's novel as an exercise in working through various issues pertinent to post-Marxist thought, including the possibility and desirability of autonomy for art, the relevance of a 'crude' materialist approach to a capitalist system increasingly driven by predominantly immaterial labour, and the impact of the 'linguistic turn' in Marxist critique. To do so, I use both the final, published version of DeLillo's Underworld, and the notes, annotations, and chapter drafts of the novel held at the Harry Ransom Center in Austin, Texas, which provide a unique insight into DeLillo's own instabilities and insecurities while writing the novel. The article concludes with a brief look at how these debates are further addressed by DeLillo in his later twenty-first century work, specifically 2004's Cosmopolis .